Faktor – Faktor yang Berhubungan Dengan Keberadaan Jentik Nyamuk Aedes Aegypti di RT 03 Kelurahan Air Lintang Wilayah Kerja Puskesmas Muara Enim Tahun 2023 - Ragah Perdaha; Fera Meliyanti; Elwa Candra; Fera Novitry (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Background:The presence of larvaeTemples of the Egyptiansin an area is an indicator of the presence of a mosquito populationTemples of the Egyptians in that area. Mosquito breeding placeTemples of the Egyptiansgreatly affects the level of density or density of larvae. Mosquito breeding placeTemples of the Egyptiansnamely the place where the mosquitoes areTemples of the EgyptiansLaying eggs can be found indoors and outdoors.Objective: knowing the factors related to the presence of mosquito larvae temples of the Egyptians In RT 03, Air Lintang sub-district, Muara Enim Health Center working area in 2023. Method :This type of research uses quantitative correlation with an approach cross sectional where data for both variables is collected at the same time or at one time. In this study, there is a relationship between 3M's actions, water storage and solid waste.Results :From the results of the analysis, it is known that the 3 M Action is related to the presence of Mosquito LarvaeTemples of the EgyptiansIn Air Lintang Village, Muara Enim Community Health Center Work Area in 2023, 98 respondents were found to have experienced the presence of mosquito larvae.Temples of the Egyptians there were 48 (49%) respondents who were smaller than respondents who did not have larvae egyptians as many as 50 (51%) respondents. And it is known that of the 98 respondents, it was found that 46 (46.9%) respondents did not carry out 3M Actions well, compared to 52 (53.1%) respondents who did 3M Actions well. 98 respondents found that 44 (44.9%) respondents had smaller water reservoirs compared to 54 (55.1%) respondents who did not have water reservoirs outside the house. 98 respondents found solid waste of 53 (54.1%) respondents which was greater than that of 45 (45.9%) respondents who had no solid waste.Conclusion :Test results chi square obtained p value 0.000 (≤0.05) means that there is a meaningful relationship between Action 3M and the presence of larvae temples of the Egyptians. Test results chi square obtained p value 0.000 (≤0.05) means there is a significant relationship between water reservoirs and the presence of mosquito larvaeTemples of the Egyptians. Test results chi square obtained p value 0.000 (≤0.05) means there is a significant relationship between solid waste and the presence of larvae egyptians.